TAX PLANNING IN PUBLIC ORGANIZATIONS AS A FORM OF COST REDUCTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The main objective that led to the preparation of this work is to determine the tax regime that best fits the company making lower your taxes always being supported by legislation. The development of this study was based on literature searches in books, laws, articles and magazines and was also carried out a case study developed in a company located in the city  of Londrina, where we applied the tax planning based on real  information.  It  was  established in the tax Simple National Income in Real and Assumed Income, may conclude that  the National was  the single tax  regime that best  fit  the   company,   according   to   their peculiarities, generating cost savings.Keywords: Tax Planning. Regimes of Taxation. Taxes. Cost-Cutting.